Graduate Employability 2.0 : Enhancing the connectedness of learners, programs and higher education institutions : final report. - Bridgstock, Ruth (Australia. Dept of Education, Skills and Employment, 2020)
This fellowship, Graduate Employability 2.0, set out to support the Australian higher education sector to foster learners’ capabilities to capitalise upon the affordances of digital and analogue social networks for professional and career development. By recognising the centrality of social relationships to all aspects of learning and work in the networked economy and society (Bridgstock, 2016), the fellowship sought to take a different and complementary approach to graduate employability rather than the ‘individual skills development’ approach currently dominant in higher education. The fellowship established empirically the opportunity for connectedness learning in higher education—it asked which learning and teaching approaches are best suited to fostering these capabilities and networks, and which fundamental institutional-enabling strategies are required to support better networked learning and teaching. It also engaged with learning stakeholders across the higher education sector in Australia to increase understanding and adoption of connectedness learning, and provided capacity-building opportunities and resources to support this. The fellowship comprised four phases in total. The fellowship’s original program of activities comprised three overlapping phases. Phase 1 focused on a comprehensive literature, policy and environmental scan to establish the roles that digital and face-to-face relationships, networks and social capital play in graduate careers, and characterise current higher education practice relating to this. It also characterised the current ‘state of play’ in relation to the connectedness of learners, programs and higher education institutions through student surveys and interviews and case studies with educators, alumni and industry representatives. Phase 2 focused on analysing and synthesising findings from phase 1, and culminated in the development of a Connectedness Learning Model, principles for connectedness, an educator’s toolkit and a range of supporting resources. Phase 3 concentrated on disseminating and sharing of the outcomes of phases 1 and 2 across the higher education sector, and embedding connectedness learning responsively at different levels of educational practice and policy at 18 universities. An additional, post-funded Phase 4 involved in-depth mentoring of ten teams of educators across Australia to embed connectedness learning into their practice and institutions. [Publisher summary, ed]